2019
DOI: 10.3390/ma13010128
|View full text |Cite
|
Sign up to set email alerts
|

Strength and Micro-Mechanism Analysis of Cement-Emulsified Asphalt Cold Recycled Mixture

Abstract: The strength of EACRM (emulsified asphalt cold recycled mixture) is closely related to the properties and proportion of raw materials. In this paper, the strength formation mechanism of EACRM was first studied through microscopic analysis, and the influence regular of aggregate gradation, emulsified asphalt, water consumption, cement consumption, and other factors on its strength was analyzed through a series of laboratory tests. The analysis results show that the asphalt binder plays the role of cementing mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 28 publications
0
11
0
Order By: Relevance
“…The evaporation residue of emulsified asphalt prepared by electric furnaces causes the aging of the evaporation residue, which easily affects test results. In order to reflect the demulsification process of emulsified asphalt [ 2 ], the evaporation residue of emulsified asphalt was prepared using the low-temperature evaporation method of ASTM D7497-09. The specific method is illustrated in Figure 3 .…”
Section: Experimental Details and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The evaporation residue of emulsified asphalt prepared by electric furnaces causes the aging of the evaporation residue, which easily affects test results. In order to reflect the demulsification process of emulsified asphalt [ 2 ], the evaporation residue of emulsified asphalt was prepared using the low-temperature evaporation method of ASTM D7497-09. The specific method is illustrated in Figure 3 .…”
Section: Experimental Details and Methodsmentioning
confidence: 99%
“…The cold recycling technology of emulsified asphalt plant mix is energy saving and environmentally friendly, and can utilize recycled asphalt pavement (RAP) materials in large quantities, so it is a research hotspot in the field of road engineering at home and abroad [ 1 , 2 , 3 , 4 ]. Emulsified asphalt cold recycled mixture has problems such as low initial strength, poor crack resistance after molding, and insufficient water stability.…”
Section: Introductionmentioning
confidence: 99%
“…The most common stabilization agents include emulsified asphalt, foamed asphalt, and cement [14,20,21]. Factors influencing the volumetric and mechanical properties of CRM were intensively investigated by many researchers, e.g., curing time and temperature [22][23][24], compacting method [25], cement content and type [26][27][28][29][30], RAP source and content [31,32], asphalt content [27,[33][34][35], gradation [21,25,36], water content [28,37], rejuvenator content [38], additive or active fillers [18,19,39,40], asphalt type, and extra aggregates [41]. At the same time, the effect of RAI or composite RAP/RAI on the performance, mechanical behavior, and small strain characteristic of CRM stabilized by emulsified asphalt or cement has been studied by many scholars [42,43].…”
Section: Introductionmentioning
confidence: 99%
“…Unger et al [ 20 ] mixed emulsified asphalt as a recycling agent with 100% reclaimed asphalt pavement (RAP) to form a new test section of pavement base, used a falling weight deflectometer (FWD) to detect its structure, and concluded that the method of using emulsified asphalt to regenerate RAP asphalt mixtures is relatively reliable. Pi et al [ 21 ] investigated the strength formation mechanism of emulsified asphalt cold recycled mixtures and analyzed the influences of the gradation, emulsified asphalt content, cement content and other factors on the performance of the cold recycled mixtures; the optimal amounts of emulsified asphalt and cement in RAP material were determined through testing. When cement is used as the regeneration agent of a recycled mixture base, higher cement contents can effectively improve the compressive strength of the mixture [ 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%